Basophil activation test is a complementary tool in the diagnosis of immediate reactions to platinum salts and taxanes - Bogas, Gador; Ariza, Adriana; Vázquez-Revuelta, Paula; Labella, Marina; Madrigal-Burgaleta, R.; Fernández-Santamaría, Rubén; Calvo-Serrano, Silvia; Villar-Chamorro, Esther; Martín-Clavo, Susana; Lebrón-Martín, Clara; Mayorga Mayorga, Cristobalina; Doña, Inmaculada; et al. (Wiley, 2024)
Background Delabelling pathways offer confirmatory diagnosis and can prevent unnecessary second-line therapies or drug desensitization procedures after chemotherapeutic hypersensitivity reactions (CHT-HSRs). However, these pathways rely on risky in vivo tests. Data on whether in vitro tests could be helpful are scarce. We assessed the role of basophil activation test (BAT) in the diagnosis of HSRs to platin salts (PSs) and taxanes (TXs) in a well-defined population featuring varied endophenotypes and severities of HSRs. Methods We conducted a 3-year-long multicentric, prospective study with 121 suspected-immediate CHT-HSR patients. The allergy workup included clinical history (initial reaction based on Type I, cytokine release syndrome, and mixed phenotype's symptoms and if unable to fit in any of these, as “indeterminate”), skin testing (ST), and drug provocation testing (DPT), provided risk assessment was favorable. Final diagnosis classified patients as “hypersensitive,” “non-hypersensitive,” or “inconclusive.” We performed BAT using CD63 and CD203c as activation markers in patients and controls. Patients underwent DPT regardless of BAT results to prevent bias. Results ST positivity significantly correlated with skin involvement, Type I phenotype, cancer recurrence, and lifetime exposures before reactions. DPTs were negative in all indeterminate phenotype patients (p = .02) and those considered low-risk, whereas they were negative in 62% moderate-risk patients. 55% were confirmed as hypersensitive (mainly Type I reactions, p < .0001), 24% as non-hypersensitive (mainly TXs and indeterminate phenotypes), and 21% as inconclusive. BAT showed 79% sensitivity in Type I IgE-mediated reactions to PSs with a high correlation to ST.
Keywords: Cáncer - Quimioterapia; Medicamentos - Ensayos; Biomedicina; Basophil activation test; Chemotherapy; Drug provocation tests; Endophenotype; Skin tests